Sistem Pendukung Keputusan Penerimaan Calon Siswa Baru MIN 40 Aceh Besar Berbasis Web - Rifai, Muhammad; Akbar, Rizaldi; Nurrisma (Jurnal Manajemen Sistem Informasi (JMASIF), 2025)
MIN 40 Aceh Besar is an Islamic education school under the Ministry of Religious Affairs of the Republic of Indonesia, located in Desa Punie, Darul Imarah District, Aceh Besar Regency, Aceh Province. The current information system used is simple, relying on a manual registration book for new student admissions. This process is inefficient, and the storage of documents is poorly organized, leading to data repetition across multiple files due to unstructured procedures. This study employs a system development methodology for designing a web-based decision support system for new student admissions. Data collection is done through literature review, observation, and interviews. The system is developed using HTML, PHP, CSS, and JavaScript, with an integrated database. The system aims to streamline data management and improve the completeness of student identity information, thus facilitating smoother data circulation. By connecting the data directly to the database, staff can easily manage student identity information and registration payments. The system’s implementation shows time efficiency in data entry, reporting, and monitoring. The outputs produced by the system include student registration reports, parent/guardian identity reports, and payment invoices, which help save time, reduce data entry errors, and simplify the search for student identity data.